Pictogram Design of Objects in The University of National Development “Veteran” of East Java Environment - Widyasari; Sutejo; A. N. Yunisya (Future Science)
Universitas Pembangunan Nasional “Veteran” Jawa Timur (University of National Development “Veteran” of East Java, subsequently referred to as UPN “Veteran” of East Java in this paper) has several signature objects within the perimeter of the university’s environment, such as physical objects (tools, things, places) and non-physical objects (action, activity, information). Those signature objects can be visualized into symbol or pictogram that signify the ideas and simplify the physical shape of the real object. Pictograms can serves as a visual language to communicate a message or information that will be easily understood by the audience. One optimization form for the use of pictogram is as the signage in the implementation of visual communication media in the UPN